2014
DOI: 10.1080/02699931.2014.911143
|View full text |Cite
|
Sign up to set email alerts
|

Experiential avoidance and well-being: A daily diary analysis

Abstract: Experiential avoidance (EA) is a regulatory strategy characterised by efforts to control or avoid unpleasant thoughts, feelings and bodily sensations. Most studies of EA have used trait measures without considering the effects of EA on psychological functioning in naturalistic settings. To address this gap, we used daily diary methodology to examine the influence of EA of anxiety on everyday well-being. For two weeks, 89 participants provided daily reports of EA, positive and negative affect, enjoyment of dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 26 publications
5
57
0
3
Order By: Relevance
“…Indeed, depressed individuals may enjoy positive daily life events (i.e., experiencing hedonic pleasure) when experiential avoidance is low, whereas they show impaired reactivity when avoidance is high (Hershenberg, Mavandadi, Wright, & Thase, ). Experiential avoidance can thus dampen pleasant emotions and exacerbate unpleasant ones (Machell, Goodman, & Kashdan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, depressed individuals may enjoy positive daily life events (i.e., experiencing hedonic pleasure) when experiential avoidance is low, whereas they show impaired reactivity when avoidance is high (Hershenberg, Mavandadi, Wright, & Thase, ). Experiential avoidance can thus dampen pleasant emotions and exacerbate unpleasant ones (Machell, Goodman, & Kashdan, ).…”
Section: Discussionmentioning
confidence: 99%
“…This emotion regulation process comprises two related components: unwillingness to remain in touch with aversive private experiences (including bodily sensations, emotions, thoughts, memories, and behavioural predispositions) and action to change aversive experiences or the events that trigger them (Hayes & Smith, 2005). Furthermore, previous research using a naturalistic approach of experiential avoidance found that it is a context-specific regulatory strategy (Machell, Goodman, & Kashdan, 2015). The experience of an infertility diagnosis and the difficulties of medical treatment may lead to intensification of negative self-referential thoughts and depressive or anxiety feelings.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that daily assessments of experiential avoidance were a stronger predictor of daily well-being than the AAQ scores, measured daily. This indicates that mediational processes may be context speci c [71]. Related to these measurement issues, there is conceptual confusion about the actual content measured with the AAQ-II that was suggested to measure acceptance and experiential avoidance, but also psychological exibility [34].…”
Section: The Role Of Decentering As An Underlying Mechanismmentioning
confidence: 99%